1975
DOI: 10.1111/j.1699-0463.1975.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Mycoplasmas in the Urinary Tract of Patients With Chronic Pyelonephritis

Abstract: Two groups of patients, each consisting of 40, were investigated for the occurrence of mycoplasmas in the urethra, bladder and upper urinary tract. Mycoplasmas were isolated significantly more frequently from the bladder urine of patients with chronic pyelonephritis than from patients with non‐infectious urinary tract diseases. Furthermore, mycoplasmas were isolated from the upper urinary tract of 5 patients with chronic pyelonephritis, while mycoplasmas could not be cultivated from the upper urinary tract of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
3

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
1
8
0
3
Order By: Relevance
“…This was simillar to other previous reports (Thomsen, 1978a;1978b;Thomsen and Lindskov, 1979). It might be due to the high sensitivity of mycoplasma (pH, temperature and materials present in culture media and clinical specimens; (Humburg et al, 2011) as well as a loss of viability during specimen collection and/or transport, furthermore, mycoplasma antibody response is one of the criteria for diagnosing the disease and antibiotic inhibition is sometimes difficult to determine (Taylor-Robinson,1996a;Amirmozafari et al, 2009;Abdul-Wahab, 2010;Abdul-Wahab and Al Sunaidi, 2013), Further research studies are needed for rapid detection of the Mycoplasma hominis in patients with the urinary tract diseases using other diagnostic method such as PCR assay that was described as rapid altrinatives to culture for the detection of of M. hominis and Ureaplasma species (Cunningham et al, 2013).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This was simillar to other previous reports (Thomsen, 1978a;1978b;Thomsen and Lindskov, 1979). It might be due to the high sensitivity of mycoplasma (pH, temperature and materials present in culture media and clinical specimens; (Humburg et al, 2011) as well as a loss of viability during specimen collection and/or transport, furthermore, mycoplasma antibody response is one of the criteria for diagnosing the disease and antibiotic inhibition is sometimes difficult to determine (Taylor-Robinson,1996a;Amirmozafari et al, 2009;Abdul-Wahab, 2010;Abdul-Wahab and Al Sunaidi, 2013), Further research studies are needed for rapid detection of the Mycoplasma hominis in patients with the urinary tract diseases using other diagnostic method such as PCR assay that was described as rapid altrinatives to culture for the detection of of M. hominis and Ureaplasma species (Cunningham et al, 2013).…”
Section: Discussionsupporting
confidence: 76%
“…The prevalence of Mycoplasmas in women with lower uriary tract symptoms (30.3%) was statistically significant and higher than in the group without lower urinary symptoms (14.5%) (p = 0.011). A study conducted by (Thomsen, 1978a;1978b) resulted in Mycoplasma hominis being detected from the upper uriary tract in 7 out of a group of 80 infected patients with acute pyelonephritis and from 0 of 60 of the control patients group with noninfectious diseases of the urinary tract. On comparing the infected and control groups, the result was found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the mycoplasmal flora of the human urethra and bladder has been the subject of numerous investigations (3, 7, 8, 10,15,17) only a few studies of the occurrence of mycoplasmas in the upper urinary tract have been reported (11, 16,17).…”
mentioning
confidence: 99%